The relationship between motivation in the working environment and the job satisfaction among the support staff in Shorefield SDN. BHD. / Nurdiana Ibrahim - Ibrahim, Nurdiana (2018)
The purpose of this study was to examine the relationship between motivation in the working environment and job satisfaction among the support staff in Shorefield Sdn. Bhd. The research method used for this study is quantitative by having 100 respondents to participate in answering the questionnaires. Convenience sampling technique was used in this study. From 100 questionnaires that have been distributed only 80 respondents returned and were considered usable questionnaires. This finding shows that the relationship between all the variables is positive and significance relation with job satisfaction. Furthermore, Physiological Needs, Social Needs and Self-Esteem Needs demonstrated a strong, positive and significance relationship towards job satisfaction. Whereby, Security Needs and Self-Actualization Needs show moderate, positive and significance relationship towards job satisfaction. As a conclusion, all the independent variables which are physiological needs, security needs, social needs, self-esteem needs and self-actualization needs have the relationship with job satisfaction.